Spatial Data Infrastructures and the Semantic Web of Spatial Things in Australia - McMeekin, David; West, Geoffrey (IEEE, 2012)
Spatial Data Infrastructures have recently become a crucial part of national infrastructures. Example users are governments using them to make informed policy decisions and the private sector using them in order to understand their customers better. It is estimated that Australian spatial industry revenue is in excess of $1.35 billion annually. The Cooperative Research Centre for Spatial Information in Australia is currently working with the Commonwealth, jurisdictions and the private sector to understand the research required in this area to support both the public and private sectors in their decision and policy making based upon these infrastructures. This paper presents an early perspective as to possible research areas in this field. An underlying theme that reoccurs in the research is the need to consider usability of such systems and the need to move beyond just data to orchestration of processes to obtain derived products.